The Improvement of Nutritional Characteristics and Antioxidant Potential of Cowpea Flour Through Germination, Roasting and ItsCombinations - Agus Setiyoko; Yuli Perwita Sari (Agroindustrial Technology Journal, 2023)
Cowpeas are a particular kind of legume and containthe second highest protein after soybeans. Cowpea is inadequate because it has antinutritions such as tannins, phytic acid, and trypsin inhibitors. Pretreatment is necessary to lower anti-nutritional elements and increase the nutrition of cowpeas' ability to be digested. This study was done to determine the effect of various pretreatment techniques on enhancing cowpea flour's nutritional qualities and antioxidant potential. A completely randomized design with one factorial and three analytical replications was done. The findings of this study demonstrate that cowpea flour may be made using a variety of pretreatments, including germination, roasting, or its combination. A combination of germination treatment followed by roasting at 1400C for 40 minutes can significantly reduce the phytic acid, tannin, and color content and increase the yield and density of the cowpea flour produced. In addition, the initial treatment with the combination had the highest protein content of 46.88%, the highest total phenol, and the most increasedRadical Scavenging Activity(RSA) or antioxidant activity of 47.00%. The most effective method to produce cowpea flour withthe best nutritional properties and antioxidant potential is a combination of germination and roasting processes as a pretreatment